ANALISIS SISTEM SALURAN PEMASARAN KACANG TANAH (Arachis hypogaea) DI KABUPATEN BONE - Yuslinda Yuslinda; Nurliani Karman; Ida Rosada (AGROTEK: Jurnal Ilmiah Ilmu Pertanian, 2021)
Research related to the analysis of the peanut marketing system has been carried out with the aim of knowing the marketing channel system, analyzing the marketing margin, farmer's share, and the profit ratio of peanuts in Cina distric, Bone Village and analyzing the efficiency of their marketing. This research was conducted in the District of China, which is the center of Peanuts in Bone Regency, starting from February to May 2020. The data in this study came from 2 data, namely primary data and secondary data. Primary data is obtained from observations and results of commissioners and secondary data is data derived from other supporting data from books, journals and other written sources. From the research conducted, it was found that the results of Peanut Marketing in China District, Bone Regency, there were two channel patterns of the two channels, the second most efficient marketing channel is through farmers who sell to retailers to consumers and the large number of farmers cannot influence the market price.